ROAD algorithm for control charts / Gejza Dohnal - Dohnal, Gejza (2015)
In statistical process control, procedures are applied that require relatively strict conditions for their use. If such assumptions are violated, these methods become inefficient, leading to increased incidence of false signals. Therefore, a robust version of control charts is sought to be less sensitive with respect to a breach of normality and independence in measurements. Robust control charts, however, usually increase the delay in the detection of assignable causes. This negative effect can, to some extent, be removed with the aid of an adaptive approach. We introduce a new adaptive version of the zone chart: The decision rule is based on exceeding the lower or upper control limits (LCL, UCL), the same as in the Shewhart-type chart. These limits will be changed adaptively in each inspection time in dependence on current state of monitored process. The algorithm can be applied to a variety of classical control charts. Using with robust control chart we obtain a robust adaptive control chart (ROAD). The comparison between different types of control charts using the RARLC index on the contaminated data clearly shows that, in the case of contaminated data, the improved ROAD is the best choice.